Gustave Rolin-Jaequemyns and the making of modern Siam : the diaries and letters of King Chulalongkorn's general adviser - Tips, Walter E. J.; Rolin-Jaequemyns, Gustave, 1835-1902. (Bangkok : White Lotus, 1996)
History of Thailand, 1892-1902, based on diaries and documents of Gustave Rolin-Jaequemyns.
Includes bibliographical references (p. 481-493).
Keywords: Rolin-Jaequemyns, Gustave, -- 1835-1902.; Thailand -- History -- 1782-1945.